Smartphone use in Neurology: a bibliometric analysis and visualization of things to come - Tatum, William O.; Acton, Emily K.; Freund, Brin; de la Cruz Gutierrez, Manuel; Feyissa, Anteneh M.; Brigham, Tara (Frontiers in Neurology, 2023)
Background and objectives Smartphones are a ubiquitous part of society with increasing use as a healthcare tool. We aimed to analyze the published literature on smartphone usage within the field of Neurology to define the scientific landscape and forecast future research initiatives. Methods We performed a bibliometric review of smartphone uses in Neurology based on a search of two Web of Science databases from inception through September 16, 2022. This librarian-guided review was conducted using Bibliometrix for data assessment and visualization. Temporal trends in publications, citation counts, collaborations, and author affiliations were among key metrics evaluated. VOS viewer identified hot spots based on generating co-occurrences and bibliographic coupling mapping. Results Our search found 3,920 publications. The U.S. produced the most topic-based publications, collaborating most frequently with U.K., Canada, and China-based authors. The most prolific institutions included Karolinska Institute, University of Sydney, and University of Pittsburgh. Bioelectromagnetics, Stroke, and Neurology were the most cited journals. Rapid growth in scientific production occurred in recent years, including during the COVID-19 pandemic. Hotspots and keyword co-occurrence included telehealth, machine learning, and self-management. Temporal trends reflect transitioning from a focus of initial publications regarding mobile phone safety to more recent application of smartphones as “smart” tools for single modality diagnosis, monitoring, management, and treatment of neurological diseases. Discussion There has been rapid expansion of the published literature on smartphone uses in Neurology. Initial focus on smartphones and health risk has shifted to uses for neurological disease diagnosis, detection, and management, with relevance as a global interface for collaboration and clinical practice.